Pendergast : the beginning - Preston, Douglas J.; Child, Lincoln (Preston, Douglas J. Pendergast novel., 2026)
"The Agent Pendergast origin story: a golden opportunity for longtime fans and new readers to learn about Agent Pendergast's strange and shocking first case"--